Modele MARIMA w prognozowaniu cen energii na Towarowej Giełdzie Energii SA - Chodakowska, Ewa; Nazarko, Joanicjusz; Worobiej, Anna (MARIMA Models for Energy Price Forecasting at the Power Exchange in Poland, 2005)
The paper discusses application of Multivariate AutoRegressive Integrated Moving Average models for energy prices forecasting at the Day-Ahead Market at The Power Exchange in Poland. The analysis of energy prices has been carried out and at the same time there has been made an attempt to find a relation between price and its volume. On the basis of available data, a MARIMA model has been proposed which describes price as a function of its previous values and energy volume.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 142-150